Brassolis isthmia (Lepidoptera: Nymphalidae) in peach palm and coconut palm in Costa Rica. - Mexzón, Ramón G. (Agronomía Mesoamericana, 2011)
The life cycle of Brassolis isthmia was studied under field and laboratory conditions in Guapiles, Limon, Costa Rica. This study was carried out between September and November, 1994, during an insect outbreak in a peach palm plantation. During the following years were conducted observations of the butterfly feeding activities on coconut palms, in several localities of the Caribbean slopes too. Several hundred eggs and larvae in the first instar were collected and placed in groups of ten individuals, and fed with pieces of peach palm leaves of 30 x 80 mm. The number of larvae necessary to cause defoliations of 5 and 20% was calculated for each larval developmental stage. Average development took 159 days, distributed as follows: egg 20, larval 114, pupal 20, and adult 5 days. The larvae are gregarious, feed during the night and remain during the day in nests constructed with debris of dry leaves and silk. The consumption rate during the larval stage was of 820.62 cmÇ; the seventh instar accounts for 72.8% of this.